Factors associated with low back pain in workers: the influence of anthropometric measures, abdominal endurance and hip flexibility - Portela Bruno Sergio; Vulczak Anderson; Queiroga Marcos Roberto (Sciendo, 2015)
Study aim: to compare the physical fitness of bus drivers and fare collectors (working hours per day in sitting position = 7h) with and without low back pain. The subjects consisted of sixty-six bus drivers and fare collectors working in a public transport company.